2019
DOI: 10.1200/jco.2019.37.15_suppl.4001
|View full text |Cite
|
Sign up to set email alerts
|

ARTIST 2: Interim results of a phase III trial involving adjuvant chemotherapy and/or chemoradiotherapy after D2-gastrectomy in stage II/III gastric cancer (GC).

Abstract: 4001 Background: Adjuvant chemotherapy and/or chemoradiotherapy have been the standard of care in GC for years, supported by randomized trials. We compared the efficacy of different chemotherapy regimens and chemoradiotherapy in patients with D2-resected, stage II/III, node-positive GC. Methods: From Feb 2013 through Nov 2018, we randomly assigned, in a 1:1:1 ratio, patients with pathologically-staged II or III, node-positive, D2-resected GC, to receive adjuvant S-1 (40-60 mg twice daily 4-weeks-on/2-weeks-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…In a retrospective investigation conducted in Korea, patients with stage III GC in the XELOX group demonstrated no improvement in survival compared with the S‐1 group; however, subgroup analysis suggested that XELOX may be associated with a better 3‐year OS rate for patients with stage IIIC GC (55.2% vs 39%; HR = 0.5; 95% CI, 0.23–1.10; P = 0.075) 18 . In the ARTIST 2 study, 3‐year DFS rate in the S‐1 group was shorter than that in the SOX group for patients with stage II and III GC with lymph node metastasis (64% vs 78%; HR = 0.617; P = 0.0157); 19 however, its effects on OS are yet to be reported. In this study, the 3‐year OS rate of patients with stage IIIC disease in the SOX group was 65.8%, which was higher than that of 59.1% reported for patients with locally advanced disease receiving S‐1 monotherapy in the ACTS‐GC study 14 .…”
Section: Discussionmentioning
confidence: 90%
“…In a retrospective investigation conducted in Korea, patients with stage III GC in the XELOX group demonstrated no improvement in survival compared with the S‐1 group; however, subgroup analysis suggested that XELOX may be associated with a better 3‐year OS rate for patients with stage IIIC GC (55.2% vs 39%; HR = 0.5; 95% CI, 0.23–1.10; P = 0.075) 18 . In the ARTIST 2 study, 3‐year DFS rate in the S‐1 group was shorter than that in the SOX group for patients with stage II and III GC with lymph node metastasis (64% vs 78%; HR = 0.617; P = 0.0157); 19 however, its effects on OS are yet to be reported. In this study, the 3‐year OS rate of patients with stage IIIC disease in the SOX group was 65.8%, which was higher than that of 59.1% reported for patients with locally advanced disease receiving S‐1 monotherapy in the ACTS‐GC study 14 .…”
Section: Discussionmentioning
confidence: 90%
“…However, subset analysis indicated the potential benefit of adjuvant chemoradiotherapy in node-positive locally advanced gastric cancer [41], and the ARTIST 2 trial was conducted to investigate the superiority of S-1 plus oxaliplatin or S-1 plus oxaliplatin with chemoradiotherapy to S-1 monotherapy in patients with node-positive stage II/III gastric cancer. The results showed the superiority of S-1 plus oxaliplatin (HR 0.617; p = 0.016) and S-1 plus oxaliplatin with chemoradiotherapy (HR 0.686; p = 0.057), but did not show an additional effect of radiotherapy on the doublet regimen [42].…”
Section: Standard Treatment In Other East Asian Countriesmentioning
confidence: 94%
“…As first reported at the American Society of Clinical Oncology annual meeting in 2019, post-operative SOX significantly prolonged DFS over S-1 with well tolerated toxicities at interim analysis. This was sufficient evidence for the independent data monitoring committee to stop the trial [48]. Despite post-operative chemoradiotherapy's promising benefit for patients with LN-positive GC in the preceding ARTIST trial, no other benefit was observed in the SOX+RT arm in the ARTIST-II trial [48].…”
Section: The Standard Treatment In the East Asiamentioning
confidence: 97%
“…At present, the guidelines in Europe and the USA recommend D1 resection, with D2 resection being an option that should be used sparingly and only by expert surgeons in specialized and high-volume centers [39,40]. The reported frequencies of patients receiving D2 gastrectomy for resectable GC in clinical trials of adjuvant therapy were 10-55% in the West [41][42][43] and 98-100% in the East [44][45][46][47][48][49][50] (Table 1). The 5-year OS rate of patients receiving curative gastrectomy without adjuvant treatment was reported at approximately 70% in Japanese and Korean trials [51,52] and 23-35% in Western trials [36,41,42].…”
Section: Differences In Surgical Outcomes Between Eastern and Westernmentioning
confidence: 99%